European principles of inhibitor management in patients with haemophilia - Giangrande, P L F; Hermans, C; O'Mahony, B; de Kleijn, P; Bedford, M; Batorova, A; Blatný, J; Jansone, K; European Haemophilia Consortium (EHC) and the European Association for Haemophilia and Allied Disorders (EAHAD) (Orphanet journal of rare diseases, 2018)
BACKGROUND: In spite of recent major advances in the understanding and treatment of inhibitor development in patients with haemophilia, multidisciplinary management of many of these patients remains suboptimal and highly heterogenous across Europe. METHODS: Following a series of multidisciplinary meetings and a review of the literature, the European haemophilia community of health professionals and patients jointly defined practical optimum standards for ensuring and harmonizing treatment and care for patients with an inhibitor. RESULTS: Ten complementary principles for the management of inhibitors in haemophilia have been developed, emphasizing the importance and benefits of a centralized, multidisciplinary, expert and holistic approach. CONCLUSIONS: This document will serve as a benchmark to improve the multidisciplinary and practical management of patients with inhibitor. Implementation and adherence to each of these principles should have a major positive impact on the management and outcomes of patients developing an inhibitor.
Keywords: hemofilie A; Bypassing agents; Evropa; Europe; Immune tolerance; Inhibitors; Haemophilia; Guidelines; Factor VIII; lidé; Hemophilia A; faktor VIII; Factor IX; Humans; faktor IX